Revolutionizing English Learning: Unleashing the Power of WhatsApp - A Dynamic Literature Exploration - Wahyuningsih, Sri; Erinawati, Ag. Eka; Wulandari, Eka Septiana; Fadila, Liana Nur; Febrianthi, Putri Rizqya (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2023)
In the teaching and learning process, WhatsApp is an application frequently utilized for online learning due to its easy operability across all levels of education. Researchers have concentrated on assessing the effectiveness of WhatsApp in English lessons by scrutinizing studies on communication technology utilizing WhatsApp. The data utilized in this literature review comprises articles published in open-access journals, allowing the authors to analyze them. Five relevant studies are under review, as discussed by Ahmed (2019), Hashemifardnia, Namuziandot, and Eshafani (2018), Minalla (2018), Novianto (2017), and Ta 'Amneh (2017). The results indicate that incorporating WhatsApp into English learning can aid learning. However, there are both advantages and disadvantages associated with its usage. The primary disadvantage is the limited internet fees students must bear to access WhatsApp. Conversely, the advantages include students' increased motivation to learn English and enhanced vocabulary and writing skills through discussions in WhatsApp groups.